2003
DOI: 10.1213/01.ane.0000081725.81280.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preoperative Inflammation on the Analgesic Efficacy of Intraarticular Piroxicam for Outpatient Knee Arthroscopy

Abstract: Intraarticular administration of piroxicam along with bupivacaine improves postoperative analgesia in synovial inflammation before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…It is assumed that following local administration of the NSAID, high concentrations of the drug were achieved in the inflamed synovium as proven by the pharmacokinetic study, with potential for a more effective reduction of inflammation and/or pain. This finding is supported by the earlier report, which suggests that NSAIDs delivered via IA injection effectively inhibit the activation of peripheral nociceptors, by reducing the levels of arachidonic acid metabolites such as prostaglandins and thromboxanes in the joint tissue (Izdes et al ., 2003). NSAIDs injected intraarticularly may also reduce the pain by modifying the local inflammatory process (Unlu et al ., 2006).…”
Section: Discussionsupporting
confidence: 85%
“…It is assumed that following local administration of the NSAID, high concentrations of the drug were achieved in the inflamed synovium as proven by the pharmacokinetic study, with potential for a more effective reduction of inflammation and/or pain. This finding is supported by the earlier report, which suggests that NSAIDs delivered via IA injection effectively inhibit the activation of peripheral nociceptors, by reducing the levels of arachidonic acid metabolites such as prostaglandins and thromboxanes in the joint tissue (Izdes et al ., 2003). NSAIDs injected intraarticularly may also reduce the pain by modifying the local inflammatory process (Unlu et al ., 2006).…”
Section: Discussionsupporting
confidence: 85%
“…It was similarly found that lornoxicam resulted in lower pain scores than did bupivacaine in a randomized controlled trial of 40 patients (Fagan et al, 2003). The use of an anti-inflammatory into the joint cavity may play a role in pain control particularly when a significant inflammatory component to the intra-articular pathology is found (Izdes et al, 2003).…”
Section: Knee Arthroscopymentioning
confidence: 97%
“…(HegeScheuing et al, 1995) RCT 59 Morphine (1mg) given either intra-articularly or intravenously at the end of arthroscopy had equivalent analgesic benefit. (Izdes et al, 2003) RCT 90…”
Section: Wwwintechopencommentioning
confidence: 99%
“…It undergoes enterohepatic circulation and is primarily used to treat arthritis and other musculoskeletal conditions [10]. Piroxicam exhibits anti-inflammatory [11], analgesic [12], and antipyretic activities in animal models. The mechanism of action of piroxicam, like any other NSAID, is not completely understood but may be related to prostaglandin synthetase inhibition [13].…”
Section: Introductionmentioning
confidence: 99%